2022
DOI: 10.3389/fpsyg.2022.823682
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Discussion of Correlation Among Psychological Symptoms, Occupational Strain, and Neurotic Personality for Metro Drive

Abstract: Metro driver is the prime person who is responsible for metro operation safety. The mental health of a metro driver is very important for the operation of the subway and requires the driver to keep high mental alertness to monitor the surrounding environment and also handle emergencies under uncertain or dangerous conditions. After a long-term occupational strain, a metro driver is likely to suffer from some mental health problems, such as anxiety and depression, that ultimately threaten the lives of passenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In recent years, studies on the prevalence of psychological symptoms and associated correlators in motor vehicle drivers received some coverage ( 4 , 5 ). For example, it is reported that occupational strain, neuroticism, and psychological symptoms are all positively correlated in metro drivers ( 6 ). Also, the study reported that bus drivers were significantly more extroverted, psychotic, and neurotic than the general population; and they were more likely to suffer from somatization and phobia ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on the prevalence of psychological symptoms and associated correlators in motor vehicle drivers received some coverage ( 4 , 5 ). For example, it is reported that occupational strain, neuroticism, and psychological symptoms are all positively correlated in metro drivers ( 6 ). Also, the study reported that bus drivers were significantly more extroverted, psychotic, and neurotic than the general population; and they were more likely to suffer from somatization and phobia ( 5 ).…”
Section: Introductionmentioning
confidence: 99%